GREEN HYDROGEN PRODUCTION FROM PALM BIOMASS : A REVIEW ON POTENTIALS AND CHALLENGES - Shahidul, Islam (Publications International Lahore, Pakistan, 2022)
This review aims to unlock information on the hydrogen production potential of carbon emission potential palm biomass and its related challenges. The for conducting this study, 100 journals were studied published between the years 2010 to 2022. for this paper is the literature review. Journal papers studied for this review published on the energy potential of EFB and technologies used for green hydrogen production from that biomass. The calorific value of EFB varies between 17 to 21 MJ (kg-EFB)-1 on a dry basis with 0.24 kgCO2eq emission. Experiments on pyrolysis and gasification demonstrated that at optimum operating conditions, the H2 yield was 127 gH2 (kg-EFB)-1. The caloric value of hydrogen is about 150MJ (Kg-H2)-1. Information published in this paper on hydrogen production from palm biomass would be a reference for researchers in preparing a methodology for green hydrogen production. This information would also attract government agencies and industries to implement a palm biomass-based hydrogen economy. This study concludes that a palm biomass-based hydrogen economy may empower Southeast Asian countries to achieve economic (SDG 8) and environmental sustainability (SDG 13) for reducing climate change effects.